Population-based prevalence, incidence, and disease burden of autoimmune hepatitis in South Korea. - Bo Hyun Kim; Hwa Young Choi; Moran Ki; Kyung-Ah Kim; Eun Sun Jang; Sook-Hyang Jeong (PLoS ONE)
Background and aim Little is known about population-based epidemiology and disease burden of autoimmune hepatitis (AIH). The aim of this study was to investigate the prevalence, incidence, comorbidity and direct medical cost of AIH in South Korea. Methods The data was from the nationwide, population-based National Health Insurance Service claims database and the Rare Intractable Disease registration program. Age and gender-specific prevalence rates were calculated, and data on comorbidity, diagnostic tests, prescribed drugs, and medical costs were retrieved for patients registered under the disease code K75.4 (AIH) from 2009 to 2013. Results A total of 4,085 patients with AIH were identified between 2009 and 2013 with a female-to-male ratio of 6.4. The age-adjusted prevalence rate was 4.82/100,000 persons and gender adjusted prevalence rates were 8.35 in females and 1.30 in males. The age-adjusted calculated incidence rate was 1.07/100,000 persons (gender-adjusted 1.83 in females and 0.31 in males). Ascites, variceal bleeding, and hepatocellular carcinoma were found in 1.4%, 1.3%, and 2.2% of the patients, respectively. Forty-six patients (1.1%) underwent liver transplantation during the study period. Case-fatality was 2.18%. Corticosteroid and azathioprine were prescribed in 44.1% and 38.0% of prevalent patients with AIH in 2013, respectively. The nationwide total direct medical cost was less than 4.0 million USD, and the average cost for each patient was 1,174 USD in 2013. Conclusion This is the first report on the nationwide epidemiology of AIH in Korea, and it showed a lower prevalence than that of Western countries with considerable disease burden.